Characterisation of the progression of salts in walls of earthen architecture heritage. (17th August 2022) - Tavares, Alice; Magalhães, M. Clara F.; Soares, Rosário; Costa, Aníbal
Abstract: Two hundred years (1750–1950) of earthen architecture represents an important period of construction in the central region of Portugal. Earthen architecture is usually built close to the coast or to rivers and placed in sandy ground. The impact of rising damp is a general problem and efflorescences are a common cause of damage decay. This problem was studied in a building with two types of earthen construction, adobe masonry walls and formed masonry walls. The aim of this research was to characterise the conditions for the appearance and phase transitions of thénardite and mirabilite, and determine how to prevent progression of salt effects in the two types of wall to support future conservation measures. Laboratory capillarity and porosimetry tests with dolomitic air lime mortar and hygrothermal monitoring were pursued along with in situ tests. Visual assessment showed that the progression of salts depends on the composition of the earthen materials. To understand these differences, all crystalline solid phases were analysed by powder X-ray diffraction, and building interior hygrothermal conditions were monitored. An investigation into the influence of surface lime water painting and sacrificial mortar application on the crystallisation of sodium sulfates concluded that these also depend on the wall's composition. Data allowed us to conclude that inside the building the temperature and humidity [relative humidity (RH = 100 p w / p °w > 70)] conditions led to the adobe breakdown by the fast conversion from thénardite to mirabilite. Therefore, contact with wet atmospheres should be avoided and interior hygrothermal conditions should be controlled. Laboratory and in situ tests showed that the environmental conditions of the spaces had effects on the results. The results contribute to understanding of the salt progression and pattern of decay, as well as supporting future recommendations for building conservation, based on the identification of environmental conditions proper to their occurrence.